Metabolic and Evolutionary Engineering of Diploid Yeast for the Production of First- and Second-Generation Ethanol - Sun, Yang; Kong, Meilin; Li, Xiaowei; Li, Qi; Xue, Qian; Hou, Junyan; Jia, Zefang; Lei, Zhipeng; Xiao, Wei; Shi, Shuobo; Cao, Limin (Frontiers in Bioengineering and Biotechnology, 2022)
Despite a growing preference for second generation (2G) ethanol in industries, its application is severely restricted owing to a major obstacle of developing a suitable yeast strain for the fermentation using feedstock biomasses. In this study, a yeast strain Saccharomyces cerevisiae A31Z for 2G bioethanol production was developed from an industrial strain, Angel, using metabolic engineering by incorporation of gene clusters involved in the xylose metabolism combined with adaptive evolution for evolving its anti-inhibitory properties. This strain outcompeted its ancestors in xylose utilization and subsequent ethanol production, and manifested a higher tolerance against common inhibitors from lignocellulosic hydrolysates, also, it lowered the production of glycerol byproduct. Furthermore, A31Z outperformed in ethanol production using industrial hydrolysate from Dried Distillers Grains with Solubles and whole corn. Overall, this study provided a promising path for improving 2G bioethanol production in industries using S. cerevisiae.